Complete Balanced Atrioventricular Septal Defect – Results of Bi-ventricular Surgical Correction - Sobieraj, Michał; Szemień, Michał; Bednarek, Marcin; Wojtalik, Michał; Mrówczyński, Wojciech (Journal of Medical Science, 2015)
Aim. The aim of this study was to analyze the results of surgical treatment of balanced AVSD during 10-year period in a single center. The adequacy of atrioventricular valves reconstruction was scrutinized as well as risk factors for mortality, redo surgery, pulmonary hypertension incidence were assessed.Materials and method. One hundred twenty one patients underwent surgical correction of AVSD between 2004 and 2013. All patients were operated by double patch technique with the apposition zone closure. Patients’ median age was: 109 (86–151) days, body weight: 4.5 (4–5.5) kg. Down syndrome was present in 100 (82.6%) patients. Results. Early mortality equaled 17.3% (21 patients) and late mortality was 1.7% (2 patients). Pulmonary hypertension (42.9%) and heart failure (33.3%) were the main causes. Cardiopulmonary bypass time (p
Keywords: AVSD; mitral valve regurgitation; redo surgery